A Review of Myiasis in Iran and a New Nosocomial Case from Tehran, Iran. - Mahbobeh Alizadeh; Gholamreza Mowlavi; Faranak Kargar; Mehdi Nateghpour; Kamran Akbarzadeh; Maryam Hajenorouzali-Tehrani (Tehran University of Medical Sciences, 2014)
Background: Due to various climatic conditions in different parts of Iran, presenting of various kinds of human myiasis is expected. Despite of a few case series, most papers related to myiasis are case reports originated from various parts of Iran. This study discusses on different clinical features of myiasis in Iran and description of one case from Tehran as a representative to nosocomial infection in Iran. Methods: The information needed for this descriptive study was derived mainly from the digital library of Tehran University of Medical Sciences. The larvae have been identified with observing on posterior spiracles, spines of their body and anal tubercles. Results: Total number of reported myiasis cases from Iran is 77 which can be categorized clinically as furuncular, wound, ophthalmic, auricular, nasopharyngeal, oral, intestinal and genitourinary. Based on parasitological features, all myiasis agents in Iran are belonging to Calliphoridae, Sarcophagidae, Oestridae and Syrphidae flies. The case which is reporting in this paper can be mentioned as representative of nosocomial myiasis which it seems to be un- derreported because of some medicolegal reasons. Conclusion: Low number of investigations on various aspects of human myiasis, as well as incuriosity to report of the cases in disease reporting system of health minister, made the myiasis as a neglected disease.